2014
DOI: 10.7763/ijtef.2014.v5.362
|View full text |Cite
|
Sign up to set email alerts
|

HRM Practices and Employee Retention in Thailand—A Literature Review

Abstract: Abstract-An empirical study is conducted to investigate the effects of HRM practices on employee retention in Thailand's FDI manufacturing industry. HRM practices that will be covered in this research consist of compensation & benefits management and reward system, and training & development. HR Intervening, which acts as the mediating variable, will be employee engagement. As the dependent variable and an observed variable, is employee retention. Thus, the conceptual model created for this study will comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
3
23
0
4
Order By: Relevance
“…Many researchers have found that Training and development has significant relation with employee retention (Hong, Hao, Ramendran and Kadiresan, 2012; Asil, Akhlagh and Maafi 2013; Johri, Yahya and Ahmed 2012). Study by Tangthong, trimetsoontorn and Rojniruntikul (2014) examined human resource management practices (compensation and benefits, reward system and training and development) on employee retention with employee engagement as mediating variable. Study showed positive relationship with HR practices.…”
Section: Employee Trainingmentioning
confidence: 99%
“…Many researchers have found that Training and development has significant relation with employee retention (Hong, Hao, Ramendran and Kadiresan, 2012; Asil, Akhlagh and Maafi 2013; Johri, Yahya and Ahmed 2012). Study by Tangthong, trimetsoontorn and Rojniruntikul (2014) examined human resource management practices (compensation and benefits, reward system and training and development) on employee retention with employee engagement as mediating variable. Study showed positive relationship with HR practices.…”
Section: Employee Trainingmentioning
confidence: 99%
“…According to Tangthong, Trimetsoontorn, & Rojniruntikul (2014) though training & development does not have a complete role in determining employee retention, it exerts direct and indirect effects when it is combined with compensation and reward benefits. Training can be an important tool for retaining employees, but it can see that the impact of training on compensation of an employee can be very crucial for retention (Anis, Ijaz-Ur-Rehman, & Safwan, 2011).…”
Section: Training and Development And Retentionmentioning
confidence: 99%
“…Employees do not have a firm grasp of their duties or obligations without it. Learning and growth are two of the main HPHRMPs in the current business environment that can improve primary expertise, skills, superior knowledge, positive attitude and actions of employees (Tangthong et al, 2014). Training can also develop the high performance of employees and increase the https://doi.…”
Section: Training and Development And Job Performancementioning
confidence: 99%